Effect of Desflurane versus Sevoflurane in Pediatric Anesthesia: A Meta-Analysis - Jiaxuan He; Yong Zhang; Rongliang Xue; Jianrui Lv; Xiaoying Ding; Zhenni Zhang (Frontiers Media S.A., 2015)
Purpose: To compare the effect of desflurane versus sevoflurane in pediatric anesthesia by conducting meta-analysis. Methods: Studies were searched from PubMed, Medline, Springer, Elsevier Science Direct, Cochrane Library and Google Scholar up to July 2014. Weighted mean difference (WMD) or risk ratio (RR) and 95% confidence intervals (CIs) were considered as effect sizes. Heterogeneity across studies was assessed by Cochran Q test and I2 statistic. The random effects model was performed in the meta-analysis when heterogeneity was observed, or the fixed effect model was used. Review Manager 5.1 software was applied for the meta-analysis. Results: A total of 11 studies (13 comparisons) involving 1,273 objects were included in this meta-analysis. No heterogeneity was observed between studies for any comparison but for postoperative extubation time. The results showed significant differences between desflurane and sevoflurane groups for postoperative extubation time (WMD = -3.87, 95%CI = -6.14 to -1.60, P < 0.01), eye opening time (WMD = -1.11, 95%CI = -1.49 to -0.72, P < 0.01), awakening time (WMD = -4.27, 95%CI = -5.28 to -3.26, P < 0.01) and agitation (RR = 1.44, 95%CI = 1.05 to 1.96, P = 0.02). No significant differences (P > 0.05) were detected for discharge from the recovery room, oculocardiac reflex, nausea and vomiting and severe pain. Conclusions: Desflurane may have less adverse effects than sevoflurane when used in pediatric anesthesia with significantly shorter postoperative extubation time, eye opening time and awakening time as well as slighter agitation.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.